Effect of Auditor Ethics, Audit Experience, and Auditor Motivation on Internal Audit Quality - Mahmud, Muhammad Daud Bin; Quilim, Cici Aryansi; Hasan, Lisa (Shafin: Sharia Finance and Accounting Journal, 2024)
The purpose of this study is to investigate how auditor motivation, audit experience, and ethics relate to the quality of audit result as evaluated by internal supervisors in local government. This study is driven by the perception that the government's internal oversight system lacks professionalism due to its poor performance in identifying state financial management fraud. Using Partial Least Square - Structural Equation Modeling (PLS-SEM) with SmartPLS 4 to assess the research model following the distribution of a questionnaire to thirty auditors designated to examine state financial management within the Central Halmahera Regency Government's jurisdiction. The study's findings demonstrate the significance of auditor ethics, audit experience, and motivation in completing audit duties in producing high-quality audit outcomes